Budgeting for Agility: A Cross-Sectoral Analysis of Fiscal Flexibility, Forecast Accuracy, and AI Integration in Corporate and Public Financial Systems - Alnafea, Fahad (Journal of Social Sciences and Management Studies, 2026)
Traditional static budgeting models are increasingly inadequate in environments marked by volatility, technological disruption, and fiscal uncertainty. Budget flexibility—the capacity to reallocate resources responsively—has gained prominence, yet cross-sectoral empirical evidence linking flexibility, forecasting accuracy, and institutional oversight remains limited. This study examines how budget structures, AI-supported forecasting, and governance mechanisms jointly shape fiscal responsiveness and predictive alignment across corporate and public systems. Using a comparative empirical design, the analysis draws on Form 10-K filings from Microsoft, Johnson & Johnson, Procter & Gamble, and ExxonMobil (2019–2023), alongside public sector data from the Open Budget Survey 2023, the OECD Budget Practices Database, and U.S. GAO oversight reports. A four-dimensional Flexibility Index is developed to assess reallocation authority, forecast cycles, AI integration, and transparency. The findings indicate that firms with decentralized budgeting structures and embedded predictive analytics exhibit lower forecast deviations and faster resource reallocation, while capital-intensive sectors face structural constraints on adaptability. In the public sector, systems characterized by strong transparency frameworks and Medium-Term Expenditure Frameworks demonstrate higher alignment between planned and actual expenditures. AI enhances forecasting accuracy only when integrated within institutional decision cycles. Overall, the study provides a cross-sectoral empirical foundation for understanding how budget flexibility, governance, and technology interact to support resilient financial systems in uncertain economic environments.